PENEGAKAN HUKUM TERHADAP PELAKU USAHA YANG MELAKUKAN IMPOR TELEPON GENGGAM SECARA TIDAK RESMI (PERBANDINGAN HUKUM DI INDONESIA, MALAYSIA DAN JEPANG) - Malik Ibrahim (2022)
Imported goods sent to a country do not necessarily have a permit or of icial tobetraded in that country. In this study, the question that will be answered is what arethe implications for the import of unof icial cellular phones by business actorswho are sold to consumers and how law enforcement and the dif erence betweenunof icial cellular phones by business actors are sold to consumers in Indonesia, Malaysia, and Japan. This research method uses normative juridical type. Theresults of the study show dif erent legal products from each country andtheirenforcement. In Indonesia, the impact of this forgery can be detrimental tostatetax revenues as well as economic instability. Thus, it is regulated by lawfromArticle 45 and Article 46 of the Consumer Protection Law to sanction a prisonerof a maximum of 2 years with a fine of Rp. 500,000,000.00. Malaysia is alsoaf ected by this black market, namely the decline in the state deficit due tothenon-disbursement of goods taxes. Law enforcement in Malaysia refers tothecounterfeiting rules based on the CopyRight Act 1987 with a prison sentenceof not more than 5 years and a fine of money. In addition, in Japan itself has theConsumer Protection Law of 2000 and its enforcement for people who carrycounterfeit and counterfeit goods based on article 167 with a prison fine of not more than 3 years. The conclusion that can be drawn is that each country, suchasIndonesia, Malaysia, and Japan, has its own way of enforcing the lawagainst thesale of unauthorized cell phones, but the impact can be the same.